Fetching the Old Southwest : humorous writing from Longstreet to Twain - Justus, James H. (University of Missouri Press, 2004)
"For more than a quarter-century, despite the admirable excavations that have unearthed such humorists as John Gorman Barr and Marcus Lafayette, the most significant of the humorists from the Old Southwest have remained the same: Crockett, Longstreet, Thompson, Baldwin, Thorpe, Hooper, Robb, Harris, and Lewis. Forming a kind of shadow canon in American literature that led to Mark Twain's early work, from 1834 to 1867 these authors produced a body of writing that continues to reward attentive readers." "James H. Justus's Fetching the Old Southwest examines this writing in the context of other discourses contemporaneous with it: travel books, local histories, memoirs, and sports manuals, as well as unpublished private forms such as personal correspondence, daybooks, and journals. Like most writing, humor is a product of its place and time, and the works studied herein are no exception. The antebellum humorists provide an important look into the social and economic conditions that were prevalent in the southern "new country," a place that would, in time, become the Deep South." "While previous books about Old Southwest humor have focused on individual authors, Justus has produced the first critical study to encompass all of the humor from this time period. Teachers and students of literary history will appreciate the incredible range of documentation, both primary and secondary."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.